Freedom-loving writer. : Proceedings of International Multidisciplinary Scientific Remote Online Conference on Innovative Solutions and Advanced Experiments M A D I S O N W R I G H T S Organised, June 18th & 19th, 2020 In Association with Novateur Publication India's A Multidisciplinary Peer Reviewed Journal journalnx.com. ISAE-2020. Page No.: 632-637 - soatova, nodira (FILOLOGIYA UFQLARI JURNALI, 2022)
2022-yil